2018
DOI: 10.1186/s12885-018-4552-x
|View full text |Cite
|
Sign up to set email alerts
|

Survival after the diagnosis of breast or colorectal cancer in the GAZA Strip from 2005 to 2014

Abstract: BackgroundWithin a dramatic socio-political context, cancer represents a growing health burden in the Gaza Strip. We investigated the survival experience of people diagnosed with breast (BC) or colorectal (CRC) cancer from 2005 to 2014.MethodsData included 1360 BC cases (median age 55.1 years) and 722 CRC cases (median age: 59.5 years; 52.5% men) recorded by the Gaza Cancer Registry according to a standard protocol. Clinical information was available for cases diagnosed in 2005–2006 only. Survival probabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 15 publications
(15 reference statements)
1
23
1
Order By: Relevance
“…The 5-year survival rate varies widely among countries, from 53% in South Africa to 89% in the United States of America [10]. The 5-year survival rate was reported to be 60–65% among Jordanian and Saudi Arabian women [11], 65.1% in the Gaza Strip [12], and 70% in Iran [13]. In return, it is better in developed countries: 82% in Europe [14] and 89% in the USA [15].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-year survival rate varies widely among countries, from 53% in South Africa to 89% in the United States of America [10]. The 5-year survival rate was reported to be 60–65% among Jordanian and Saudi Arabian women [11], 65.1% in the Gaza Strip [12], and 70% in Iran [13]. In return, it is better in developed countries: 82% in Europe [14] and 89% in the USA [15].…”
Section: Introductionmentioning
confidence: 99%
“…For patients in the Gaza Strip diagnosed with breast cancer and colon cancer from 2005 to 2014, Panato et al found they had respective 5-year survival rates of 65·1% and 50·2%. These survival rates are comparable to surrounding Arab countries during the same period, but substantially lower than high income Mediterranean countries, such as Italy or among Jewish patients in Israel [ 27 ]. The deteriorating situation in the Gaza Strip in more recent years, with further reductions in the availability of essential medicines adding to long-term lack of services and facilities for particular patient groups, has significant potential implications for the morbidity and mortality of cancer patients.…”
Section: Discussionmentioning
confidence: 82%
“…On top of that, multiple antineoplastic medications are not allowed to patients due to prohibition. 12 Even though regular prompt screening and reasonable care to the patient available in most developed countries brings a better outcome, but, many other factors play a significant role. Studies have shown that the outcome of CRC is determined by various factors, including the American Joint Committee on Cancer AJCC staging, tumor location, and neoadjuvant/adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%